BIM for Construction Site Logistics Management - Whitlock, K.; Abanda, F.H.; Manjia, M.B.; Pettang, C.; Nkeng, G.E. (Journal of Engineering, Project, and Production Management, 2018)
Emerging Building Information Modelling (BIM) has been hailed as a revolutionary technology and information management process that facilitates collaboration and more efficient design and construction processes through innovative 3D modelling software, open access to information and multidisciplinary integration. The deadline of compliance to BIM level 2 on all public sector centrally procured construction projects has expired leaving many construction firms anxious to adopt BIM. Most common documented applications of BIM have been in the areas of architectural and structural design, quantity surveying, construction project management, and sustainability with very limited peer-reviewed studies on construction logistics management. The aim of this study is to investigate how BIM can be applied to construction logistics management. This study adopts a desk-top approach, with articles sources from renowned scientific databases such as ScienceDirect, Google Scholar and Emerald. The study culminated in the identification of benefits and barriers of adopting BIM for construction logistics management. Given only a desk-top approach has been used, the recommendation for future study is to build on this to conduct an empirical study using both qualitative and quantitative data. This will provide an in-depth understanding of the use of BIM for construction logistics management and open opportunities for further research.